Cover Image. Issue 2 (21st March 2023) - Ohmi, Aki; Tanaka, Miho; Rinno, Jun; Tsuboi, Masaya; Chambers, James K.; Uchida, Kazuyuki; Goto‐Koshino, Yuko; Tomiyasu, Hirotaka; Ohno, Koichi; Tsujimoto, Hajime
Abstract : Cover caption : The cover image is based on the Original Article Clinical characteristics and outcomes of Mott cell lymphoma in nine miniature dachshunds by Aki Ohmi et al., https://doi.org/10.1002/vms3.975 .